Evaluation of the American yam bean (Pachyrhizus spp.) for storage root yield across varying eco-geographic conditions in Uganda - Andiku, C.; Tukamuhabwe, Phineas; Ssebuliba, J.M.; Talwana, Herbert A.L.; Tumwegamire, Silver; Grüneberg, W.J. (Canadian Center of Science and Education, 2019)
The American yam bean (Pachyrhizus spp.) is a legume crop that is exclusively used for its storage roots. The seeds are inedible due to presence of toxic rotenone. It produces high storage root yields comparable of major root crops like cassava or sweetpotato. And flower pruning more than doubles its root yield performance. Using twenty five yam bean accessions, the current study aimed to determine root yield stability and adaptability, and presence of yam bean production mega environments in Uganda. Trials were planted at three stations, Namulonge, Serere, and Kachwekano during two consecutive seasons of 2011. Fresh storage root yields were significantly different (p < 0.05) across locations with the ideal location being Namulonge (fresh storage root yield of 10.1 t ha-1), followed by Serere (8.0 t ha-1), and Kachwekano (3.1 t ha-1). Results of AMMI analysis indicated the presence of genotype-by-environment interaction for fresh storage root yield. Through AMMI estimates and GGE visual assessment, genotype 209017 was the highest yielding with mean yield of 20.7 t ha-1. Genotype 209018 with mean yield of 15.5 t ha-1 was the most stable and adapted accession in the entire discriminating environment in Uganda. From the environmental focusing plot, the six environments were grouped into two putative mega environments for yam bean production.